Fundamentals of Physics, Part 4, Chapters 34-38, Enhanced Problems Version, Sixth Edition - Halliday David (Wiley, 2002)
The priciple goal of this book is to provide instructors with o tool by which they can tech students how to effectively read scientific material and successfully reason through scientific questions.